Experimental investigation of convective heat transfer coefficient of various agricultural products under open sun drying - Akpinar, EK (Taylor & Francis Inc, 2004)
In this article, the convective heat transfer coefficients of various agricultural products were investigated under open sun drying conditions. Data obtained from open sun drying experiments for eight agricultural products, namely, mulberry, strawberry, apple, garlic, potato, pumpkin, eggplant, and onion were used to determine values of convective heat transfer coefficient. The value of convective heat transfer coefficient was determined as 1.861 W/m(2)degrees C for mulberry, 6.691 W/m(2)degrees C for strawberry, 11.323 W/m(2)degrees C for apple, 1. 136 W/m(2)degrees C for garlic, 8.224 W/m(2)degrees C for potato, 8.613 W/m(2)degrees C for pumpkin, 6.981 W/m(2)degrees C for eggplant, and 6.767 W/M(2)degrees C for onion. The experimental error in terms of percent uncertainty was also calculated.
Keywords: convective heat transfer; open sun drying; agricultural product